Model of Improving Tourism Industry Performance through Innovation Capability - SARI, Yunita; MAHRINASARI, Mahrinasari; AHADIAT, Ayi; MARSELINA, Marselina (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019DO - 10.14505//jemt.10.4(36).16, 2019)
The capability of innovation is an important factor for the economic performance of tourism companies, (Martínez-Román et al. 2015). This study aims to examine the influence of innovation capabilities on product innovation and process innovation and then these results influence marketing performance. The design of the research is explanatory research with a quantitative approach. The population of this research is 168 starred hotels in southern Sumatra, the data used are primary data. Processing data used a structural equation model. The conclusion of this study shows that the capability of innovation influences product innovation and process innovation, which in turn influences marketing performance.